Analisis Rendahnya Minat Baca dan Gerakan Literasi Sekolah - Boy Setyawan Zalukhu; Reymon Putra Saroni Zalukhu (CV. SINAR HOWUHOWU, 2024)
This research explores the root causes of low student interest in reading and the vital role of the school literacy movement as a solution. Factors such as an unsupportive learning environment, the high price of books, the influence of gadget technology and a low literacy culture are the mainchallenges. The desk research method was used to analyze academic sources, identify the causes and impacts of low interest in reading and the role of the school literacy movement. Findings show a complexity of factors, including a lack of literacy culture and ineffective school literacy activities, exacerbating the problem. In addition, the results show that interest in reading is also affected by the lack of support from families and the lack of infrastructure to support literacy activities in schools. The school literacy movement emerged as a strategic solution with an integrated approach, improving reading skills, forming a positive literacy culture and involving the community. The implementation of this movement has been proven to increase student participation in literacy activities, improve reading skills and facilitate collaboration between the school, family andcommunity. This study underlines the importance of joint efforts through the school literacy movement in overcoming the challenge of low student interest in reading, not only as a concrete solution but also as a shaper of a positive literacy culture in the community.